Successful reimplantation of extruded bone segment in lower limb open fractures: case report and literature review - Hu, Xiongke; Tan, Qian; Zhu, Guanghui; Liu, Kun (Frontiers in Pediatrics, 2024)
The aim of this study is to summarize and demonstrate the different sterilization methods and surgical techniques for open fractures with impacted bone segments in the lower limbs. Methods: A retrospective analysis was conducted on the clinical characteristics, treatment methods, and outcomes of a case involving a 10.5 cm extruded segment of the femur in a 9-year-old male with a right femoral comminuted fracture treated at our center. Additionally, a retrospective review and summary were conducted on all reported cases of open fractures with impacted bone segments in the lower limbs. Results: Our center treated a 9-year and 11-month-old male child who presented with a Gustilo type IIIB open fracture of the femur along with a large segment of the femur being ejected as a result of a car accident. The child was resuscitated to correct hypovolemic shock, underwent emergency wound debridement, and had Ilizarov external fixation of the femur. The ejected femur segment was sterilized using ethylene oxide and re-implanted four days after the injury. A literature review showed that out of the cases of open fractures with impacted bone segments in the lower limbs, there were 14 cases involving the femur and 5 cases involving the tibia. Among them, sterilization was performed using povidone-iodine in 6 cases, high-pressure steam sterilization in 3 cases, and other methods including gamma-ray irradiation and soaking in antibacterial solution were used in the remaining cases. In terms of surgical methods, 7 cases were fixed with locking plates, 3 cases were fixed with external fixation devices, 1 case was immobilized in a cast, 1 case was fixed with an intramedullary rod, and 4 cases involved a combination of external fixation and internal fixation. The average time for re-implantation was 7.6 days after the injury. There were no serious complications such as infection or non-union observed in any of the cases during follow-up. Conclusion: Ethylene oxide can be considered a reliable choice for the reimplantation of displaced bone segments in open fractures after sterilization.